THE CONTENT AND ESSENCE OF THE SERVICE OF A PSYCHOLOGIST IN PROFESSIONAL EDUCATION - Musayeva Umida Khaidarovna (American Journals Publishing, 2024)
In this article, the organization of psychological service activities in professional education, including the use of modern information and communication technologies in work activities, to increase the efficiency of the work of directing students to the profession, the abilities, skills, interests and to help them choose the right profession based on their professional inclinations, to psychologically monitor the personal, mental and social development of students at different ages, to identify psychological defects in education, to determine what happens in their mental development prevention of any possible negative deviations, early diagnosis and recommendations.
Keywords: psychological service, correction, prevention, psychological consultation, psychological-pedagogical diagnosis.